Analisis Strategi Pengembangan Kompetensi SDM Pada Pelaku UMKM Jajanan Tradisional Pasar Karang Jasi - Sugiantari, Ni Nengah; Candra, Edy (Universitas Islam Kadiri, 2025)
This study aims to analyze employee competency development in traditional snack UMKM located in Pasar Karang Jasi, focusing on experiential learning and mentoring by the business owner. The phenomenon underlying this study is the limited employee competence, lack of formal training, and the dominant role of the owner, which create a gap between required skills and actual employee abilities. A descriptive qualitative method was employed, using in-depth interviews with three employees (Intan, Dayu, and Nengah) and one business owner (Reni), supported by direct observation of production activities. Thematic analysis was applied to identify core aspects of competency development, such as independence, creativity, motivation, and related challenges. The results show that hands-on practice and mentoring enhance technical and non-technical skills, self-confidence, and work motivation. However, limitations in time, resources, and dependence on the owner remain obstacles to independence. This research contributes to the literature on human resource development in UMKM and offers practical insights for owners to design effective and sustainable employee development strategies. Appropriate human resource development improves competence while strengthening UMKM sustainability and competitiveness.